Circulating inflammatory and neurotrophic markers as moderators and/or mediators of cognitive remediation outcome in people with bipolar disorders - Rebecca Strawbridge; Dimosthenis Tsapekos; Allan H. Young (BJPsych Open, 2024)
Background Immune dysregulation appears involved in affective disorder pathophysiology. Inflammatory biomarkers have been linked with the cognitive impairment observed in people with bipolar disorders and as such are candidate markers that may improve with, and/or predict outcomes to, cognitive remediation therapies (CRT).